Skład narodowościowy, wyznaniowy i językowy ludności województwa łódzkiego w II Rzeczypospolitej - Rzepkowski, Arkadiusz (Przegląd Nauk Historycznych, 2011)
This article describes national, religious and language frame of society in the city of Łódź within the twenty years’ interwar period. The base for the researches were the results described in the censuses from 1921 and 1931. Another source of information were the statistics made by Łódź Statistical Department, Ministry of Social Care and District Departament acting on behalf of Łódź Voivodship Of fice existing at that time. Łódź voivodship, while existence of Polish Republic II, was a multi national conglomerate made of Poles, Jews and the Germans. Where Poles and the Ger mans were the dominating group there especially in villages. In towns there was a great percentage of Jews. Villages were not inhabited as numerously as towns by them. In the area of Łódź voivodship its inhabitants were Catholics mostly, followers of Judaism were a great group too, Protestants were the smallest part of its inhabitants. The role of Catholics became stronger in religious structure thanks to Orthodox Jews and Protestants. It was strongly connected with growth in the presence of Polish people in that area. Most of the people living there declared Polish language as their mother tongue. It was determined by national structure of the region. Especially in towns a certain percentage of people declared Yiddish or Hebrew language. The smallest number of people declared German language as their mother tongue.